Clinical and Onychoscopy Patterns in Fingernail Onychomycosis—A Study by the International Dermoscopy Society Trichoscopy And Onychoscopy Task Force - Iorizzo, Matilde; Piraccini, Bianca Maria; Alessandrini, Aurora; Bruni, Francesca; Vollono, Laura; Pampaloni, Francesca; Gioia Di Chiacchio, Nilton; Di Chiacchio, Nilton; Jimenez-Cahue, Juan; Grover, Chander; Apalla, Zoe; Souissi, Asmahne; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: Onychomycosis is one of the most common nail diseases. Fingernail onychomycosis is significantly less frequent than toenail onychomycosis and it is often misdiagnosed due to its subtle clinical presentations. Objectives: We sought to analyze the clinical and onychoscopic features of culture-proven cases of fingernail onychomycosis in adult and pediatric patients. Methods: Medical records of 120 patients with onychomycosis limited to the fingernails were collected and analyzed across several dermatological centers (Italy, Switzerland, Spain, Greece, Brazil, India, Morocco, Tunisia). Data collected included age, sex, affected hand, affected fingernails, isolated fungal microorganism, clinical, and onychoscopic signs. Results: A total of 341 fingernails were analyzed. The most commonly affected hand was the right one ,and the most frequently affected digits were the second and third. The mean number of affected digits per patient was 2.84. Cultures identified Trichophyton rubrum in 54 cases, T. mentagrophytes var. interdigitalis in 20 cases, Aspergillus spp. in 8 cases, Candida spp. in 31 cases, and various other fungi in the remaining cases. Major clinical and onychoscopic features observed included onycholysis, subungual hyperkeratosis, leukonychia, chromonychia and absence of the cuticles. On the basis of all findings, 4 main types of fingernail onychomycosis were identified. Conclusions: Fingernail onychomycosis presents with distinct clinical and onychoscopy characteristics that can overlap with other nail conditions. Dermoscopy enhances diagnostic accuracy, but mycological confirmation is mandatory for a definitive diagnosis.